Sunstorm - Clarke, Arthur C. (Arthur Charles), 1917-2008.; Baxter, Stephen; Orion Books (London : Orion Books, 2006)
Bisesa Dutt tries to discover why she was returned to Earth in the year 2037 by the Firstborn amidst the turmoil of an approaching apocalypse.
Publisher's Weekly
Adult.
Adult
Keywords: Space and time -- Fiction; Science fiction; Space and time -- Fiction; Science fiction